Dinamika Masyarakat Urban - Elok Maria Ulfah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The problem examined in this study is: how the change dynamics of religious and socio-cultural patterns in an urban community, Tanggul Rejo, Porong District, Sidoarjo Regency, can be elaborated from the perspective of community development ?. To uncover the problem, this study used a phenomenological approach emphasizing human’s action in a social relationship and mutual interaction in terms of providing and understanding meaning. In addition, this study employed qualitative methods, enriched by direct and intensive involvement of researchers on the field. Related to data collection, this study utilized in-depth interview techniques, documentation, and observation. The collected data thus was analyzed by an iterative (continuous) strategy which was developed further during the research process. The strategy was conducted through some crucial steps: the elaboration of research problem, data collection, data reduction, data presentation, the process of drawing conclusions, and verifying the data. The findings indicate that the urban community at the research setting has a lack of religious knowledge, resulting to changes in their religious behavior and lifestyle in the daily activities. Additionally, this situation could impact on the residential development sector. Moreover, their behavior patterns also generate the fading of the trust in other communities although these communities have desire to contribute in the development sector in the urban area of Tanggul Rejo. The deviation of behavior patterns in the urban community of Tanggul Rejo apparently also influences significant changes in their socio-cultural system, which leads to the emergence of hedonist and westernist behaviors. Based on this phenomenon, community development strategies have been advocated by some agents of change implementing such various strategies as a religious approach and being involved in the infrastructure and moral development process in this community.